To Inherit the Earth: The Landless Movement and the Struggle for a New Brazil - French, John D. (Revista Mundos do Trabalho, 2009)
Book review: WRIGHT, Angus and WOLFORD, Wendy. To Inherit the Earth:The Landless Movement and the Struggle for a New Brazil. Oakland, CA: Food First Books, 2003